A DINÂMICA DO CONHECIMENTO NA CONSTRUÇÃO DE UMA UNIVERSIDADE EMPREENDEDORA: POTENCIALIDADES E FRAGILIDADES OBSERVADAS NA UNIVERSIDADE FEDERAL DE PERNAMBUCO - Paulo Sergio Oliveira do Nascimento (Universidade Federal de Santa Catarina, 2016)
The present study aims to reflect on the potentialities and weaknesses for the emergence of an Entrepreneurial U niversity, based primarily on research conducted at the Universidade Federal de Pernambuco (UFPE) in 2013 and 2015. We set out herein to highlight the production and dissemination of knowledge, innovation, knowledge society, management and bureaucracy as the structural links of the academic and institutional relationship with both the market and society. We therefore address the dynamics of knowledge and its relevance within the context of globalization and current society, as well as the changes that affect the state and redefine its role. The study adopted a qualitative case study methodology, drawing on data analysis using the Toulmin mod el of argumentation (2001) applied to the abovementioned research. The findings of this reflection highlight the relevance and topicality of the studies by Henry Etzkowitz (2009) on the university - industry - government (Triple Helix) relationship, and Peter Evans (2004) regarding state structures and state - society relations, in explaining key aspects in the process of economic and social development.